PREHYPERTENSION AND RISK FOR ALL-CAUSE AND CARDIOVASCULAR MORTALITY BY DIABETES STATUS: RESULTS FROM THE NATIONAL HEALTH AND NUTRITION EXAMINATION SURVEYS. (April 2021) - Huang, Jiayi; Yu, Yuling; Lin, Lin; Chen, Chaolei; Shen, Geng; Huang, Yuqing; Lo, Kennth; Feng, Yingqing
Abstract : Objective: The objective of this study was to investigate whether the association between prehypertension and all-cause and cardiovascular mortality was related to diabetes status. Figure. No caption available. Design and method: Totally 26070 participants aged >= 18 years were all from the 1999–2014 National Health and Nutrition Examination Surveys (NHANES). Prehypertension was defined as systolic/diastolic blood pressure: 120–139/80-89 mmHg. Participants were followed up for all-cause and cardiovascular mortality until 31 December 2015. Cox proportional hazards models, sensitivity analyses and Kaplan-Meier survival curves were conducted. Results: Overall, 15295 (58.67%) of participants did not have diabetes and prehypertension, 8870 (34.02%) had prehypertension alone, 835 (3.20%) had diabetes alone, and 1070 (4.11%) had both diabetes and prehypertension. Compared with participants without either diabetes or prehypertension, the multivariable adjusted hazard ratios for all-cause mortality among participants with prehypertension alone, diabetes alone, and both diabetes and prehypertension were 1.08 (95% CI: 0.95, 1.23), 1.26 (0.98, 1.62), and 1.67 (1.38, 2.03)(P for trend<0.001), as well as for cardiovascular mortality were 1.40 (95% CI: 0.92, 2.14), 2.21 (1.12, 4.38), and 2.87 (1.65, 4.99)(P for trend<0.001), respectively. The associations were robust in the subgroup analysis. Conclusions: Our findings suggested that prehypertension with an increased risk for cardiovascular and all-cause mortality based on diabetes status.